P-, I-, g-, and D-Angles in Normed Spaces - Hendra Gunawan; Janny Lindiarni; Oki Neswan (Institute for Research and Community Services (LPPM) ITB, 2008)
The notion of angles is known in a vector space equipped with an inner product, but not well established in a vector space equipped only with a norm. In this note, we shall develop some notions of angles between two vectors in a normed space and discuss their properties.